Do impulsive individuals benefit more from food go/no-go training? Testing the role of inhibition capacity in the no-go devaluation effect. (1st May 2018) - Chen, Zhang; Veling, Harm; Dijksterhuis, Ap; Holland, Rob W.
Abstract: Not responding to food items in a go/no-go task can lead to devaluation of these food items, which may help people regulate their eating behavior. The Behavior Stimulus Interaction (BSI) theory explains this devaluation effect by assuming that inhibiting impulses triggered by appetitive foods elicits negative affect, which in turn devalues the food items. BSI theory further predicts that the devaluation effect will be stronger when food items are more appetitive and when individuals have low inhibition capacity. To test these hypotheses, we manipulated the appetitiveness of food items and measured individual inhibition capacity with the stop-signal task. Food items were consistently paired with either go or no-go cues, so that participants responded to go items and not to no-go items. Evaluations of these items were measured before and after go/no-go training. Across two preregistered experiments, we consistently found no-go foods were liked less after the training compared to both go foods and foods not used in the training. Unexpectedly, this devaluation effect occurred for both appetitive and less appetitive food items. Exploratory signal detection analyses suggest this latter finding might be explained by increased learning of stimulus-response contingencies for the less appetitive items when they are presented among appetitive items. Furthermore, the strength of devaluation did not consistently correlate with individual inhibition capacity, and Bayesian analyses combining data from both experiments provided moderate support for the null hypothesis. The current project demonstrated the devaluation effect induced by the go/no-go training, but failed to obtain further evidence for BSI theory. Since the devaluation effect was reliably obtained across experiments, the results do reinforce the notion that the go/no-go training is a promising tool to help people regulate their eating behavior.